Pandemic boredom: little evidence that lockdown-related boredom affects risky public health behaviors across 116 countries - Westgate, Eric C; Buttrick, Nicholas R; Lin, Yijun; Helou, Gaelle El; Agostini, Maximilian; Belanger, Jocelyn J; Gutzkow, Ben; Kreienkamp, Jannis; Abakoumkin, Georgios; Abdul Khaiyom, Jamilah Hanum; Ahmedi, Vjollca; Akkas, Handan; et al. (American Psychological Association, 2023)
Some public officials have expressed concern that policies mandating collective public health behaviors (e.g., national/regional “lockdown”) may result in behavioral fatigue that ultimately renders such policies ineffective. Boredom, specifically, has been singled out as one potential risk factor for noncompliance. We examined whether there was empirical evidence to support this concern during the COVID-19 pandemic in a large cross-national sample of 63,336 community respondents from 116 countries. Although boredom was higher in countries with more COVID-19 cases and in countries that instituted more stringent lockdowns, such boredom did not predict longitudinal within-person decreases in social distancing behavior (or vice versa; n = 8,031) in early spring and summer of 2020. Overall, we found little evidence that changes in boredom predict individual public health behaviors (handwashing, staying home, self-quarantining, and avoiding crowds) over time, or that such behaviors had any reliable longitudinal effects on boredom itself. In summary, contrary to concerns, we found little evidence that boredom posed a public health risk during lockdown and quarantine.